DETERMINAN STRUKTUR MODAL DAN STRUKTUR HUTANG PADA PERUSAHAAN ANGGOTA JAKARTA ISLAMIC INDEX DI BEI - Najmudin Najmudin (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2014)
The purpose of this paper is to examine the causality of determinants on capital structure and debt lifetime. This study investigates 30 companies of Jakarta Islamic Index (JII) that have been listed on the Indonesian Stock Exchange (IDX) over a three-year period. In total, 30 companies of JII are qualified to be included in the study sample according to the availability and continuity of published financial statements. Variables used for the analysis include leverage ratios (total debt (TD), and long-term debt (LTD)), profitability, growth, firm size, age, asset structure, and liquidity. The panel character of data allows for the use of panel data methodology. Panel data involves the pooling of observations on a cross-section of units several times. The regression analysis has shown that TD ratio is positively influenced by GRT and LIQ, and negatively by ROA, and has no significant causality from SIZ, AGE, and TAN. On the other hand, LTD ratio is positively influenced by SIZ, TAN, and LIQ, and negatively by ROA, and has no significant causality from GRT and AGE.